The Extent of Gender Gap in Citations in Ophthalmology Literature - Cao, Suqi; Xiong, Yue; Zhang, Wenhua; Zhou, Jiawei; He, Zhifen (Frontiers in Medicine, 2022)
Purpose: To investigate the severity and causes of gender imbalance in the counts of ophthalmology citations. Methods: The PubMed database were searched to identify cited papers that were published in four journals (Prog Retin Eye Res, Ophthalmology, JAMA Ophthalmol, Invest Ophthalmol Vis Sci) between August 2015 and July 2020, and those that referenced these cited papers by 2021 July (i.e., citing papers). Gender category of a given paper is defined by the gender of the first and last author (MM, FM, MF and FF; M means male and F means female). A generalized additive model to predict the expected proportion was fitted. The difference between the observed proportion and expected proportion of citations of a paper gender category was the primary outcome. Results: The proportion of female-led (MF, FF) papers slightly increased from 27% in 2015 to 30% in 2020. MM, FM, MF and FF papers were cited -9.3%, -1.5%, 13.0% and 23.9% more than expected, respectively. MM papers cited 13.9% more male-led (MM, FM) papers than female-led papers and FF papers cited 33.5% fewer male-led papers than female-led papers. The difference between the observed proportion and expected proportion of MM citing papers within male-led and female-led cited papers grew at a rate of 0.13% and 0.67% per year. Conclusions: The high frequency of citations of female-led papers might narrow the gender gap in the citation count within ophthalmology. These findings show that papers by female-led are less common, so the gender gap might still exist even with their high citation count.